Situation Report: Baltic Area, 5 October 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The New First Secretary's New Agenda, Part I: A National Communist Program / by Toomas Ilves The First Secretary's New Agenda, Part II: A Program of Reform / by Toomas Ilves The Draft Program of the People's Front of Latvia / by Dzintra Bungs The Latvian SSR Government Reorganized: An Interim Report / by Dzintra Bungs A protest at the Ignalina Atomic Power Plant / by Saulius Girnius Police Disperse Demonstrations / by Saulius Girnius Soviet Lithuanian Historians Show Unprecedented Objectivity about the Republic's Past / by Kestutis Girnius Lithuanian Dissent: Proud Past, Uncertain Future / by Kestutis Girnius The Catholic Church in 1988 / by Saulius Girnius